THE EFFECT DESCRIBE AND DRAW TECHNIQUE TOWARD STUDENTS’ SPEAKING SKILL - Suldania Pratiwi; Sri Erma Purwanti; Agus Mustajib (Program Studi Pendidikan Bahasa Inggris, 2021)
Speaking skill is one of the skills that students need to have. However, there are several factors that make students not master speaking, that was students feel ashamed to express opinions, afraid to make mistakes. One of them in students of MTsN 3 Indragiri Hilir. This problem is the background of the problem in this research. To find out the effect of describing and drawing techniques, researchers used experimental research with pre-experimental designs. The data collection technique in this research was a test using the oral test as an instrument. The sample of this research was 25 students of VII MTsN 3 Indragiri Hilir. After getting the data using the oral test, the researcher found that describe and drawing technique given an effect on students’ speaking skills, the score of the post-test (76.44) was better than the pre-test (66,32), and indicated by some factors, students more active, enjoy, brave. And with the result, t-observed was 22.0 while the t-table was 2.06 to 5. % and 2.81 for 1%. The t-observed score was higher than the t-table. Based on the result, H0 (null hypothesis) is rejected and H1 (alternative hypothesis) is accepted. It also means that describe and draw technique was given effect on students' speaking skills at grade VII of MTsN 3 Indragiri Hilir in academic years 2020/2021.